2015
DOI: 10.1111/jdv.12949
|View full text |Cite
|
Sign up to set email alerts
|

Co‐existence of psoriasis and melanoma in a large urban academic centre population: a cross‐sectional retrospective study

Abstract: Our findings show a statistically significant association between psoriasis and melanoma. After adjusting the OR for phototherapy and age, a statistically significant association remained. Further investigations exploring these associations are warranted in order to establish the relative risk for melanoma in psoriasis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…18 A retrospective, registry-based, American study showed that there was a statistically significant association between psoriasis and melanoma and the association remained after adjusting the OR for phototherapy and age. 19 An Italian retrospective study compared a group of nondermatology patients consisting of patients needing vascular surgery and patients with psoriasis. The study demonstrated that patients with psoriasis had a significantly lower probability of having melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…18 A retrospective, registry-based, American study showed that there was a statistically significant association between psoriasis and melanoma and the association remained after adjusting the OR for phototherapy and age. 19 An Italian retrospective study compared a group of nondermatology patients consisting of patients needing vascular surgery and patients with psoriasis. The study demonstrated that patients with psoriasis had a significantly lower probability of having melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between atopy and carcinoma of the skin has been examined by several studies, with divergent results. [1][2][3][4][5][6] In the scientific literature, two underlying major concepts are discussed. The first cites allergies as a stimulant of the immune system and protective factor with respect to the development of carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between atopy and carcinoma of the skin has been examined by several studies, with divergent results . In the scientific literature, two underlying major concepts are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies associate an increased risk of certain cutaneous and lymphoproliferative malignancies with psoriasis. [123]…”
mentioning
confidence: 99%
“…[12] The risk is highest for those with severe psoriasis and also for patients treated with PUVA, methotrexate, cyclosporine, topical tar, and biologicals.…”
mentioning
confidence: 99%